Disruptive innovation and mainstreaming low-cost and low-carbon housing - Green, Jemma Marie (Curtin University, 2017)
The roles of solar-storage and modular construction technologies are analysed through case studies in Perth using disruptive innovation transition theory, evaluated by three lenses: disruptive technologies, disruptive business models and disruptive culture and behaviour change. Solar-storage will cause the emergence of low-carbon energy collaborative behaviour managed by local citizen utilities, and modular construction will undermine traditional construction industries. Both require significant digital skills. Disruptive governance will require responses to ‘fight, flight or innovate’ reactions by industry and agencies.